Survival Comparisons of Home Dialysis Versus In-Center Hemodialysis: A Narrative Review. Issue 1 (July 2019) - Vinson, Amanda J.; Perl, Jeffrey; Tennankore, Karthik K.
Purpose of review: Many observational studies have demonstrated a survival benefit with home dialysis compared with in-center dialysis; however, results have been conflicting. The purpose of this review was to identify pitfalls and limitations in existing literature and examine the challenges of studying home and in-center dialysis populations. Sources of information: Original research articles were identified from MEDLINE using search terms "in-center hemodialysis, " "home hemodialysis, " "conventional hemodialysis, " "nocturnal hemodialysis, " and "short daily hemodialysis." Methods: A focused review and critical appraisal of existing home versus in-center hemodialysis survival literature was conducted to identify potential causes for variability in the observed survival outcomes. Key findings: The controversy in existing literature stems from the challenges of randomizing patients to home versus in-center hemodialysis modalities, and therefore a reliance on observational comparisons for study. In many cases, these observational analyses have been limited by selection bias (variabilities in populations included, inclusion of both incident and prevalent cohorts, and variabilities in dialysis intensity), as well as residual confounding. Furthermore, the studies that do exist lack generalizability in many cases. Limitations: There are few randomized controlled trials examining the survival benefit of home versus in-center hemodialysis and existing observational studies are often limited by bias and reduced generalizability. These limitations comprise the body of this review. Implications: This review examines challenges surrounding survival comparisons with home versus in-center hemodialysis and identify important directions for future study.